Survival and severity in dominant cerebellar ataxias. (7th January 2015) - Monin, Marie‐Lorraine; Tezenas du Montcel, Sophie; Marelli, Cecilia; Cazeneuve, Cecile; Charles, Perrine; Tallaksen, Chantal; Forlani, Sylvie; Stevanin, Giovanni; Brice, Alexis; Durr, Alexandra
Abstract Inherited spinocerebellar ataxias (SCAs) are known to be genetically and clinically heterogeneous. Whether severity and survival are variable, however, is not known. We, therefore, studied survival and severity in 446 cases and 509 relatives with known mutations. Survival was 68 years [95% CI: 65–70] in 223 patients with polyglutamine expansions versus 80 years [73–84] in 23 with other mutations (P < 0.0001). Disability was also more severe in the former: at age 60, 30% were wheelchair users versus 3% with other SCAs (P < 0.001). This has implications for genetic counseling and the design of therapeutic trials.